Analyst Forecast Consistency - HILARY, GILLES; HSU, CHARLES (Journal of Finance, 2013)
ABSTRACT We show empirically that analysts who display more consistent forecast errors have greater ability to affect prices, and that this effect is larger than that of stated accuracy. These results lead to three implications. First, consistent analysts are less likely to be demoted and are more likely to be nominated All Star analysts. Second, analysts strategically deliver downward‐biased forecasts to increase their consistency (if at the expense of stated accuracy). Finally, the benefits of consistency and of “lowballing” (accuracy) are increasing (decreasing) in institutional investors’ presence.